Medicine, madness and murderers: the context of English forensic psychiatric hospitals - McDonald, Ruth; Furtado, Vivek; Völlm, Birgit (Emerald, 2017)
Approach: We used qualitative data collection (interviews and focus groups with staff and site visits to English forensic psychiatry hospitals) and our analysis was informed by Lefebvre’s writings on space. Purpose: The purpose of this paper is to add to our understanding of context by shedding light on the relationship between context and organisational actors’ abilities to resolve ongoing challenges. Findings: Responses to ongoing challenges were both constrained and facilitated by the context, which was negotiated and co-produced by the actors involved. Various (i.e. societal and professional) dimensions of context interacted to create tensions, which resulted in changes in service configuration. These changes were reconciled, to some extent, via discourse. Despite some resolution, the co-production of context preserved contradictions which mean that ongoing challenges were modified, but not resolved entirely. Value: The paper highlights the importance of viewing context as co-produced in a continuous manner. This helps us to delineate and understand its dynamic nature and its relationship with the everyday actions and beliefs of the organisational actors concerned.